Mini-CEX as a formative assessment tool for undergraduate medical students in ophthalmology - Hamna Khalid; Nasir Chaudhary; Asif, Nawal; Ayesha Mahmood; Zahid Kamal (Journal of the Pakistan Medical Association, 2024)
Mini-clinical evaluation exercise is a compound tool that allows assessment and feedback from a knowledgeable assessor. When it is conducted during clinical rotations, it gives the margin of improvement in skills via constructive feedback. The current study was planned to assess if mini-clinical evaluation exercise is an effective assessment tool. Starting from January 15, 2022, 80 medical students of the 4th year were enrolled, with 40(50%) of them having had conventional rotation of one month, and the other 40(50%) having had to exposure to mini-clinical evaluation exercise mini-CEX during their rotations. At the end of rotation on February 15, 2022, clinical skills of the 2 groups were assessed. The score of the intervention group having had mini-clinical evaluation exercise exposure was better than the control group. Hence, mini-clinical evaluation exercise was found to be a formative assessment tool for 4th year undergraduate medical students. Key Words: Mini-clinical evaluation exercise, Teaching learning tool, Undergraduate medical students, Ophthalmology.